Probiotic Effects on Multispecies Biofilm Composition, Architecture, and Caries Activity In Vitro - Zhihui Chen; Sebastian Schlafer; Gerd Göstemeyer; Falk Schwendicke (Microorganisms, 2020)
While probiotics have been tested for their anti-caries effect in vitro and also clinically, there is a lack of understanding of their effects on complex dental biofilms. We assessed two probiotics, Lactobacillus reuteri and Streptococcus oligofermentans, on a continuous-cultured model containing Streptococcus mutans, Lactobacillus rhamnosus and Actinomyces naeslundii. Cariogenic biofilms were grown on bovine enamel specimens and daily challenged with L. reuteri or S. oligofermentans whole culture (LC/SC) or cell-free supernatant (LS/SS) or medium only (negative control, NC) (n = 21/group) for 10 days. Biofilm was assessed via counting colony-forming units, quantitative polymerase chain reaction, and fluorescence in situ hybridization. Caries activity was determined by pH measurements and by assessing mineral loss (ΔZ) using transverse microradiography. Both LC and SC significantly reduced total and strain-specific cariogenic bacterial numbers (p < 0.05). ΔZ was reduced in LC (mean ± SD: 1846.67 ± 317.89) and SC (3315.87 ± 617.30) compared to NC (4681.48 ± 495.18, p < 0.05). No significant reductions in bacterial numbers and ΔZ was induced by supernatants. Biofilm architecture was not considerably affected by probiotic applications. Viable probiotics L. reuteri and S. oligofermentans, but not their culture supernatants, could reduce the caries activity of multi-species biofilms in vitro.